A Rare Case of Bartonella Encephalitis With Hemiplegia. (31st January 2019) - Rosas, Laura; Rao, Kavya; McGough, Christine; Becker, Ashley
The authors describe a 12-year-old girl with an atypical presentation of Bartonella encephalitis. She presented with fever and altered mental status and developed flaccid paralysis of her left upper extremity a day later. An electroencephalogram showed slowing over her right hemisphere. She had mild leukocytosis and bandemia, but her imaging and cerebrospinal studies were unrevealing. After five days, her symptoms resolved and she was discharged home on doxycycline due to suspicion for Bartonella encephalitis. The patient admitted to playing with a kitten two months prior, but she lacked the classic regional lymphadenopathy. Bartonella titers were sent during her hospitalization and returned positive after her discharge. Cat scratch disease neurologic manifestations are uncommon, with hemiplegia being exceedingly rare. This case illustrates that focal neurologic signs may develop during cat scratch disease infection and suggests that cat scratch disease encephalitis should be considered during evaluation of a pediatric patient with acute flaccid paralysis.